Patient‐specific logic models of signaling pathways from screenings on cancer biopsies to prioritize personalized combination therapies. Issue 6 (16th June 2020) - Eduati, Federica; Jaaks, Patricia; Wappler, Jessica; Cramer, Thorsten; Merten, Christoph A; Garnett, Mathew J; Saez‐Rodriguez, Julio
Abstract :